KEPENTINGAN STRATEGIS AMERIKA SERIKAT DI ASIA-PASIFIK - Poltak Partogi Nainggolan (Sekretariat Jenderal DPR RI, 2013)
Since the end of 2011, US changing policy on Asia-Pacific can be more obviously seen. President Obama, for example, has stated that US will permanently exist in the region after for long time focused its policy on Middle East and Europe. This article is part of a research report on the changing paradigm of US security policy in the Asia-Pacific region. The article is developed from a descriptive analytical research which applies a qualitative method. Data gathering is conducted by combining library studies and open in-depth interviews. Findings reveal the relevance between US national interest and the changing orientation of US security policy in Asia-Pacific.